Perovskite layer and preparation method thereof, perovskite / crystalline silicon laminated solar cell, photovoltaic module and photovoltaic system
By depositing an inorganic frame on the substrate of the perovskite layer and introducing a slit coating method of PEG derivatives containing amino groups, the deposition problem of large-area perovskite layer in industrial silicon base battery process is solved, and high quality and high quality are achieved Reproducible deposition improves the performance of perovskite solar cells.
Patent Information
- Application Number
- CN202411302359.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-17
AI Technical Summary
The prior art is difficult to achieve high-quality and high reproducibility deposition of large-area perovskite layers when compatible with the industrial silicon base battery process, which limits the industrialization process of perovskite/crystalline silicon stacked solar cells.
The inorganic frame material is deposited on the substrate of the perovskite layer to be deposited, and the organic salt solution is coated on the inorganic frame by slit coating method, introducing PEG derivatives containing amino groups to improve the viscosity and thermal diffusion coefficient of the organic salt solution. Promote the sufficient reaction of the organic salt solution with the inorganic framework to form a high-quality perovskite layer.
In compatible with the industrial silicon base battery process, high-quality and high reproducibility deposition of large-area perovskite layers is achieved, improving the photoelectric conversion efficiency and stability of perovskite solar cells.
Smart Images

Figure CN119156097A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solar cells, and in particular to a perovskite layer and a preparation method thereof, a perovskite / crystalline silicon stacked solar cell, a photovoltaic module and a photovoltaic system. Background Art
[0002] The certified power conversion efficiency (PCE) of perovskite / crystalline silicon tandem solar cells has exceeded the theoretical efficiency limit of single-junction silicon solar cells. How to promote the industrialization of perovskite / crystalline silicon tandem solar cells has gradually become a hot research direction for perovskite / crystalline silicon tandem solar cells. The key to promoting the industrialization of perovskite / crystalline silicon tandem solar cells lies in how to prepare large-area perovskite layers with high quality and high reproducibility while being compatible with the industrial silicon bottom cell process with a large velvet surface.
[0003] Currently, printing processes such as slot coating, inkjet printing, and doctor blade coating have been widely used for large-area production of perovskite solar cells. Although these methods have shown the intrinsic potential for low-cost, large-area production of perovskite films, they cannot achieve high-quality and high-reproducibility deposition of large-area perovskites while being compatible with industrial silicon bottom cell processes with large textures.
[0004] It should be noted that the above content is not necessarily prior art, nor is it intended to limit the scope of patent protection of this application. Summary of the invention
[0005] The embodiments of the present application provide a perovskite layer and a preparation method thereof, a perovskite / crystalline silicon stacked solar cell, a photovoltaic module and a photovoltaic system to solve or alleviate the technical problems raised above. The embodiments of the present application deposit an inorganic framework material on a substrate to be deposited with a perovskite layer to form an inorganic framework; then an organic salt solution is coated on the inorganic framework by a slit coating method, and the organic salt solution reacts with the inorganic framework material to form a perovskite layer; an amino-containing PEG (polyethylene glycol) derivative is introduced into the organic salt solution in the slit coating method, which can increase the viscosity of the organic salt solution and make its thermal diffusion coefficient uniform, reduce the influence of the wind knife on the shape of the curved liquid surface during the slit coating process, offset the lateral capillary flow of the solute particles, promote the full reaction of the organic salt solution with the inorganic framework, and achieve high-quality and high-reproducibility deposition of a large-area perovskite layer while being compatible with the industrial silicon bottom cell process with a large velvet surface.
[0006] To achieve the above objectives, this application adopts the following technical solutions: A method for preparing a perovskite layer, comprising: depositing an inorganic framework material on a substrate to form an inorganic framework; An organic salt solution is coated on the inorganic framework by a slit coating method, and the organic salt solution reacts with the inorganic framework material to form a perovskite layer; The organic salt solution comprises an organic salt, an organic solvent and a PEG derivative containing an amino group.
[0007] In some embodiments, the amino group-containing PEG derivative includes one or more of O-(2-aminoethyl)polyethylene glycol, O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol, O-(3-carboxypropyl)-O′-[2-(3-mercaptopropionylamino)ethyl]-polyethylene glycol, and O-(2-aminoethyl)-O′-(2-carboxyethyl)polyethylene glycol 3000 hydrochloride.
[0008] In some embodiments, the inorganic framework material includes one or more of lead iodide, lead bromide, lead chloride, cesium iodide, cesium bromide, and cesium chloride; The organic salt includes one or more of methylammonium iodide, methylammonium bromide, methylammonium chloride, formamidine hydroiodide, formamidine hydrobromide, formamidine hydrochloride, and methylammonium thiocyanate; The organic solvent includes one or more of ethanol, isopropanol and dimethyl sulfoxide.
[0009] In some embodiments, the mass ratio of the amino-containing PEG derivative to the organic salt solution is 1:20 to 1:100.
[0010] In some embodiments, the thickness of the inorganic framework is 300-600 nm.
[0011] In some embodiments, the method for preparing the inorganic framework includes: simultaneously evaporating PbI2 and CsBr by evaporation to form the inorganic framework layer; wherein the evaporation rate of the PbI2 is 1.0~1.5 Å / s, and the evaporation rate of the CsBr is 0.4~0.6 Å / s.
[0012] In some embodiments, after forming the inorganic framework and before applying the organic salt solution, the method further comprises: performing a first annealing on the substrate stacked with the inorganic framework; the conditions of the first annealing include: an annealing temperature of 130-170° C. and an annealing time of 2-10 min.
[0013] In some embodiments, in the process of coating the organic salt solution on the inorganic frame by slit coating method, the coating speed is controlled to be 20-40 mm / s, the liquid discharge speed is 20-40 µL / s, and the Gap is 60-100 µm.
[0014] In some embodiments, after applying the organic salt solution, the method further comprises: sequentially performing pre-annealing and a second annealing on the substrate coated with the organic salt solution; wherein the conditions for the pre-annealing include: an annealing temperature of 60-100° C. and an annealing time of 2-10 min; the conditions for the second annealing include: an annealing temperature of 140-170° C., an annealing time of 20-30 min, and an annealing environment of air with a relative humidity of 20-40%.
[0015] The embodiment of the present application also provides a perovskite layer, which is prepared by the above method.
[0016] The embodiment of the present application also provides a perovskite / crystalline silicon tandem solar cell, comprising the above-mentioned perovskite layer.
[0017] An embodiment of the present application further provides a photovoltaic module, which includes a plurality of solar cells connected in series and / or in parallel; wherein at least one solar cell is such as the above-mentioned perovskite / crystalline silicon tandem solar cell.
[0018] An embodiment of the present application also provides a photovoltaic system, including the above-mentioned photovoltaic component.
[0019] The above technical solution adopted in the embodiment of the present application may have the following advantages: (1) An inorganic framework material is deposited on a substrate to be deposited with a perovskite layer to form an inorganic framework; an organic salt solution is then coated on the inorganic framework using a slit coating method, and the organic salt solution reacts with the inorganic framework material to form a perovskite layer; an amino-containing PEG derivative is introduced into the organic salt solution in the slit coating method to promote the full reaction between the organic salt solution and the inorganic framework, thereby facilitating the formation of a uniform and high-quality perovskite layer.
[0020] (2) Introducing amino-containing PEG derivatives into the organic salt solution can increase the viscosity of the organic salt solution and make its thermal diffusion coefficient uniform, reduce the influence of the wind knife on the shape of the curved liquid surface during the slit coating process, offset the lateral capillary flow of the solute particles, and promote the full reaction of the organic salt solution with the inorganic framework. In addition, it can achieve high-quality and high-reproducibility deposition of large-area perovskite layers while being compatible with the industrial silicon bottom cell process with a large velvet surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the multiple drawings represent the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings only depict some embodiments disclosed in the present application and should not be regarded as limiting the scope of the present application.
[0022] Figure 1It is a schematic diagram of the structure of a perovskite / crystalline silicon tandem solar cell provided in an embodiment of the present application.
[0023] Description of reference numerals: 1. Single crystal silicon substrate; 2. First i-type a-Si:H layer; 3. First n-type a-Si:H layer; 4. Second i-type a-Si:H layer; 5. Second n-type a-Si:H layer; 6. ITO transparent conductive layer; 7. First silver electrode; 8. ITO composite layer; 9. Hole transport layer; 10. Perovskite layer; 11. LiF passivation layer; 12. C 60 Electron transport layer; 13. SnO2 buffer layer; 14. IZO transparent conductive layer; 15. Second silver electrode.
[0024] Figure 2 This is a SEM image of the perovskite layer prepared in Example 1 of the present application.
[0025] Figure 3 This is a SEM image of the perovskite layer prepared in Comparative Example 1 of the present application.
[0026] Figure 4 This is the XRD data diagram of the perovskite layer prepared in Example 1 of the present application.
[0027] Figure 5 This is the XRD data diagram of the perovskite layer prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0028] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. In the accompanying drawings, for clarity, the sizes of layers, regions, elements and their relative sizes may be exaggerated. Wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limitations on the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other.
[0029] It should be understood that when an element or layer is referred to as "on ...", "adjacent to ...", "connected to" or "coupled to" other elements or layers, it can be directly on, adjacent to, connected to or coupled to other elements or layers, or there can be intervening elements or layers. On the contrary, when an element is referred to as "directly on ...", "directly adjacent to ...", "directly connected to" or "directly coupled to" other elements or layers, there is no intervening element or layer. It should be understood that although the terms first, second, third, etc. can be used to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings of the present disclosure, the first element, component, region, layer or part discussed below can be represented as the second element, component, region, layer or part. And when the second element, component, region, layer or part is discussed, it does not mean that the present disclosure necessarily has the first element, component, region, layer or part.
[0030] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0031] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein, for example. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0032] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for broadly including quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.
[0033] The present application aims to provide a perovskite layer and a preparation method and application thereof, wherein the preparation of the perovskite layer is based on a two-step mixing method, specifically, an inorganic framework material is deposited on a substrate to form an inorganic framework; an organic salt solution is then coated on the inorganic framework by a slit coating method, and the organic salt solution reacts with the inorganic framework material to form a perovskite layer; an amino-containing PEG derivative is introduced into the organic salt solution in the slit coating method, so that the viscosity of the organic salt solution can be increased and its thermal diffusion coefficient can be uniformized, the influence of the wind knife on the shape of the curved liquid surface during the slit coating process can be reduced, the lateral capillary flow of the solute particles can be offset, and the organic salt solution can be promoted to fully react with the inorganic framework, so as to achieve high-quality and high-reproducibility deposition of a large-area perovskite layer (a large-area perovskite layer refers to a perovskite layer with an area of more than 10 cm²) while being compatible with an industrial silicon bottom cell process with a large velvet surface.
[0034] Below, exemplary embodiments of the present application will be described in more detail with reference to the accompanying drawings. It should be noted that these exemplary embodiments can be implemented in many different forms and should not be construed as being limited to the embodiments described herein.
[0035] The present application embodiment provides a method for preparing a perovskite layer, comprising: Depositing an inorganic framework material on a substrate (to be deposited with a perovskite layer) to form an inorganic framework; An organic salt solution is coated on the inorganic framework by a slit coating method, and the organic salt solution reacts with the inorganic framework material to form a perovskite layer; The organic salt solution comprises an organic salt, an organic solvent and a PEG derivative containing an amino group.
[0036] In the embodiment of the present application, the introduction of an amino-containing PEG derivative into the organic salt solution in the slit coating method can increase the viscosity of the organic salt solution and make its thermal diffusion coefficient uniform, reduce the influence of the wind knife on the shape of the curved liquid surface during the slit coating process, offset the lateral capillary flow of the solute particles, and promote the full reaction of the organic salt solution with the inorganic framework. Under the condition of compatibility with the industrial silicon bottom battery process with a large velvet surface, high-quality and high-reproducibility deposition of a large-area perovskite layer can be achieved. That is, the introduction of an amino-containing PEG derivative into the organic salt solution in the slit coating method can promote the full reaction of the organic salt solution with the inorganic framework, and can complete the high-quality conformal growth of a wide-bandgap perovskite film on an industrial large-velvet crystalline silicon substrate. In addition, in the embodiment of the present application, the amino-containing PEG (polyethylene glycol) derivative is a class of compounds that introduce an amino (-NH2) functional group on the PEG main chain.
[0037] In the embodiment of the present application, the thickness of the inorganic frame is 100-1000 nm. Exemplarily, the thickness of the inorganic frame is 100 nm, 200 nm, 220 nm, 240 nm, 260 nm, 280 nm, 300 nm, 320 nm, 340 nm, 360 nm, 380 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm or 1000 nm.
[0038] In the embodiment of the present application, the method for depositing the inorganic framework material to form the inorganic framework can be selected from one or more of chemical vapor deposition (CVD), solution method, vacuum flash evaporation assisted solution treatment method, one-step and two-step deposition method, ultrafast room temperature reactive ion etching process, coating method, and evaporation method.
[0039] In the embodiment of the present application, the selected inorganic framework material needs to match the selected organic salt solution to facilitate the reaction of the organic salt solution with the inorganic framework material to form a perovskite layer. The thickness of the perovskite layer directly affects its ability to absorb sunlight. A perovskite layer that is too thin cannot fully absorb photons in the spectrum, and a perovskite layer that is too thick may cause unnecessary light scattering and energy loss; reasonable control of the thickness and band gap of the perovskite layer can improve the absorption of sunlight by the perovskite layer, thereby improving the photoelectric conversion efficiency of the solar cell. Preferably, the thickness of the prepared perovskite layer is 500nm~1µm (for example, 500nm, 600nm, 700nm, 800nm, 900nm, 1µm), and the band gap is 1.65~1.68eV (for example, 1.65eV, 1.66eV, 1.67eV, 1.68eV).
[0040] In an optional embodiment, the amino-containing PEG derivative includes one or more of O-(2-aminoethyl)polyethylene glycol, O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol, O-(3-carboxypropyl)-O′-[2-(3-mercaptopropionylamino)ethyl]-polyethylene glycol, and O-(2-aminoethyl)-O′-(2-carboxyethyl)polyethylene glycol 3000 hydrochloride.
[0041] In the embodiment of the present application, the introduction of an amino-containing PEG derivative into the organic salt solution in the slit coating method can increase the viscosity of the organic salt solution and make its thermal diffusion coefficient uniform, reduce the influence of the wind knife on the shape of the curved liquid surface during the slit coating process, offset the lateral capillary flow of the solute particles, promote the full reaction of the organic salt solution with the inorganic framework, and achieve high-quality and high-reproducibility deposition of large-area perovskite while being compatible with the industrial silicon bottom cell process with a large velvet surface; in addition, the introduced PEG derivative contains an amino group and a C=O bond, which can well passivate the free Pb in the perovskite film. 2+ and halogen ions, improve the crystallization quality of the perovskite layer, reduce the film formation defects of the perovskite layer, and thus improve the photoelectric performance of the device including the perovskite layer.
[0042] In an optional embodiment, the inorganic framework material includes one or more of lead iodide, lead bromide, lead chloride, cesium iodide, cesium bromide, and cesium chloride; The organic salt includes one or more of methylammonium iodide, methylammonium bromide, methylammonium chloride, formamidine hydroiodide, formamidine hydrobromide, formamidine hydrochloride, and methylammonium thiocyanate; The organic solvent includes one or more of ethanol, isopropanol and dimethyl sulfoxide.
[0043] In the embodiments of the present application, the selected inorganic framework material must match the selected organic salt solution to facilitate the reaction of the organic salt solution with the inorganic framework material, thereby forming a perovskite layer with a specific band gap; limiting the types of raw materials for making the perovskite layer is conducive to allowing the inorganic framework and the organic components in the organic salt solution to fully react, thereby achieving conformal deposition of a perovskite layer with high crystal quality, low defect density, and high purity.
[0044] In an optional embodiment, the mass ratio of the amino-containing PEG derivative to the organic salt solution is 1:20-1:100 (for example, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100).
[0045] In the embodiment of the present application, an amino-containing PEG derivative is introduced into the organic salt solution in the slit coating method, which can increase the viscosity of the organic salt solution and make its thermal diffusion coefficient uniform, reduce the influence of the wind knife on the shape of the curved liquid surface during the slit coating process, offset the lateral capillary flow of the solute particles, and promote the full reaction of the organic salt solution with the inorganic framework. While being compatible with the industrial silicon bottom battery process with a large velvet surface, high-quality and high-reproducibility deposition of large-area perovskite is achieved; in addition, the introduced PEG derivative contains amino groups and C=O bonds, which can well passivate free Pb2+ and halogen ions in the perovskite film, improve the crystallization quality of the perovskite layer, and reduce the film formation defects of the perovskite layer, thereby improving the photoelectric performance of the device including the perovskite layer.
[0046] In the embodiments of the present application, the PEG derivative containing the amino group can adjust the crystallization state and morphology of the perovskite layer, and the amount of the PEG derivative containing the amino group added is regulated so that the mass ratio of the PEG derivative containing the amino group to the organic salt solution is 1:20~1:100, which can ensure the acquisition of a high-quality perovskite layer and facilitate the preparation of high-efficiency and high-stability perovskite solar cells.
[0047] In an optional embodiment, the thickness of the inorganic framework is 300-600 nm (eg, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm).
[0048] In the embodiments of the present application, the thickness of the inorganic framework is one of the important factors affecting the performance of the perovskite layer. By precisely controlling the thickness of the inorganic framework, the crystallization quality and performance of the perovskite layer can be optimized, thereby improving the photoelectric conversion efficiency and stability of the perovskite solar cell.
[0049] In an optional embodiment, the preparation method of the inorganic framework includes: simultaneously evaporating PbI2 and CsBr by evaporation to form the inorganic framework layer; wherein the evaporation rate of the PbI2 is 1.0~1.5 Å / s (for example, 1.0 Å / s, 1.1 Å / s, 1.2 Å / s, 1.3 Å / s, 1.4 Å / s, 1.5 Å / s), and the evaporation rate of the CsBr is 0.4~0.6 Å / s (for example, 0.4Å / s, 0.45 Å / s, 0.5 Å / s, 0.55 Å / s, 0.6 Å / s).
[0050] In the embodiment of the present application, an evaporation method is used to simultaneously evaporate PbI2 and CsBr to form an inorganic framework layer, and the evaporation rates of PbI2 and CsBr are controlled at the same time to make the distribution of iodine ions and bromide ions more uniform, thereby facilitating improving the film-forming crystallization quality of the perovskite layer.
[0051] In an optional embodiment, after forming the inorganic framework and before applying the organic salt solution, the method further includes: performing a first annealing on the substrate stacked with the inorganic framework; the conditions for the first annealing include: an annealing temperature of 130~170°C (for example, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C), and an annealing time of 2~10min (for example, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min).
[0052] In an embodiment of the present application, after the inorganic framework is formed and before the organic salt solution is applied, the substrate of the stacked inorganic framework is subjected to a first annealing, and the temperature and time of the first annealing are reasonably controlled. The annealing process helps to remove residual solvents and volatile components in the inorganic framework, promote crystal growth, and facilitate obtaining higher quality perovskite crystals.
[0053] In an optional embodiment, in the process of coating the organic salt solution on the inorganic frame by a slit coating method, the coating speed is controlled to be 20-40 mm / s (for example, 20 mm / s, 22 mm / s, 24 mm / s, 26 mm / s, 28 mm / s, 30 mm / s, 32 mm / s, 34 mm / s, 36 mm / s, 38 mm / s, 40 mm / s), and the liquid discharge speed is 20-40 μm. L / s (e.g., 20µL / s, 22µL / s, 24µL / s, 26µL / s, 28µL / s, 30µL / s, 32µL / s, 34µL / s, 36µL / s, 38µL / s, 40µL / s), Gap is 60~100µm (for example, 60µm, 65µm, 70µm, 75µm, 80µm, 85µm, 90µm, 95µm, 100µm).
[0054] In the embodiment of the present application, when the organic salt solution is coated by the slit coating method, the coating speed, liquid discharge speed, and Gap (the size of the gap between the upper mold updie and the lower mold downdie in the coating head) are reasonably controlled, and the coating of the organic salt solution is more uniform, which is conducive to achieving high-quality and high-reproducibility deposition of large-area perovskite layers.
[0055] In an optional embodiment, after applying the organic salt solution, the method further comprises: sequentially performing pre-annealing and a second annealing on the substrate coated with the organic salt solution; wherein the pre-annealing conditions include: an annealing temperature of 60 to 100°C (for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C), an annealing time of 2 to 10 min (for example, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min, 40 min, 41 min, 42 min, 43 min, 44 min, 45 min, 46 min, 47 min, 48 min, 49 min, 50 min, 51 min, 52 min, 53 min, 54 min, 55 min, 56 min, 57 min, 58 min, 59 min, 60 min, n, 10min); the conditions for the second annealing include: an annealing temperature of 140-170°C (for example, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C), an annealing time of 20-30min (for example, 20min, 21min, 22min, 23min, 24min, 25min, 26min, 27min, 28min, 29min, 30min), and an annealing environment of air with a relative humidity of 20-40%.
[0056] In the embodiment of the present application, after the organic salt solution is applied to form the perovskite layer, pre-annealing and second annealing are performed in sequence, and the processes of pre-annealing and second annealing are reasonably controlled. The pre-annealing and second annealing are combined to promote the full reaction of the organic salt solution with the inorganic framework, achieve high-quality and high-reproducibility deposition of large-area perovskite, and at the same time, can well passivate the free Pb in the perovskite film. 2+ and halogen ions, improve the crystallization quality of the perovskite layer, reduce the film formation defects of the perovskite layer, and thus improve the photoelectric conversion efficiency of the solar cell. The second annealing process also limits the relative humidity of the air, that is, limits the moisture content in the air, which can further promote the full reaction of the organic salt solution with the inorganic framework, and achieve high-quality and high-reproducibility deposition of large-area perovskites, thereby further improving the photoelectric conversion efficiency of solar cells. In addition, it should be noted that the pre-annealing can be carried out in a nitrogen atmosphere or in the air. When the pre-annealing is carried out in the air, there is no need to control the moisture content in the air; the second annealing needs to be carried out in an air atmosphere. During the second annealing, the moisture content in the air is controlled, that is, the relative humidity in the air is controlled, which can further promote the full reaction of the organic salt solution with the inorganic framework, and achieve high-quality and high-reproducibility deposition of large-area perovskites, thereby further improving the photoelectric conversion efficiency of solar cells.
[0057] The following specific examples further illustrate the present application, but should not be construed as limiting the present application. Without departing from the spirit and substance of the present application, modifications or replacements made to the methods, steps or conditions of the present application are within the scope of the present application.
[0058] Example 1 The perovskite / crystalline silicon stacked solar cell comprises a first silver electrode 7, an ITO transparent conductive layer 6, a second n-type a-Si:H layer 5, a second i-type a-Si:H layer 4, a single crystal silicon substrate 1, a first i-type a-Si:H layer 2, a first n-type a-Si:H layer 3, an ITO composite layer 8, a hole transport layer 9, a perovskite layer 10, a LiF passivation layer 11, and a C 60 The electron transport layer 12, the SnO2 buffer layer 13, the IZO transparent conductive layer 14, the second silver electrode 15; the structure of the perovskite / crystalline silicon stacked solar cell provided in Example 1 is as follows Figure 1 shown.
[0059] The specific preparation process of the perovskite / crystalline silicon tandem solar cell is as follows: (1) A 150 µm thick n-type polished silicon wafer was selected and placed in a KOH solution at 85°C for texturing, followed by standard RCA cleaning to remove surface organic matter and metal ions, thereby obtaining a single crystal silicon substrate 1 with a texture size of 2-5 µm; (2) depositing a 6 nm first i-type a-Si:H layer 2 and a 5 nm first n-type a-Si:H layer 3 on the front side of the single crystal silicon substrate 1 by PECVD at a deposition temperature of 200°C; (3) depositing a 6 nm second i-type a-Si:H layer 4 and a 5 nm second n-type a-Si:H layer 5 on the back side of the single crystal silicon substrate by PECVD at a deposition temperature of 200°C; (4) depositing an ITO transparent conductive layer 6 with a thickness of 100 nm on the back side by magnetron sputtering, and then depositing a first silver electrode 7 with a thickness of 300 nm by thermal evaporation; (5) Depositing an ITO composite layer 8 on the front side by magnetron sputtering with a thickness of 15 nm; (6) Prepare Me-4PACz hole transport layer 9 by spin coating method, with a thickness of about 3 nm; (7) using an evaporation method to simultaneously evaporate an inorganic framework layer of PbI2 and CsBr, and performing a first annealing on the substrate stacked with the inorganic framework. The first annealing temperature is 150°C, the annealing time is 5 min, and the thickness of the obtained inorganic framework layer is 450 nm. The evaporation rate of PbI2 is 1.4 Å / s, and the evaporation rate of CsBr is 0.5 Å / s. (8) O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol, FAI, FABr, MACl, and MASCN are dissolved in isopropanol to prepare an organic salt solution, wherein the mass ratio of the amino-containing PEG derivative (O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol) to the organic salt solution is 1:30; the organic salt solution is coated on the inorganic framework layer by a slit coating method at a coating speed of 20 mm / s, a liquid discharge speed of 20uL / s, and a Gap of 100µm; the substrate coated with the organic salt solution is pre-annealed and then annealed for the second time to prepare a wide bandgap perovskite layer 10 (Cs 0.1 MA 0.15 FA 0.75 PbI 2.4 Br 0.6 ), the band gap of the perovskite layer 10 is about 1.68 eV, and the thickness is 600nm; wherein, the annealing temperature of the pre-annealing is 90°C, the annealing time is 2min, and the annealing environment is air; the annealing temperature of the second annealing is 150°C, the annealing time is 20min, and the annealing environment is air with a relative humidity of 40%; In addition, it should be noted that the area of the perovskite layer prepared in step (8) of this embodiment is 16 cm 2 ; (9) A LiF passivation layer 11 is deposited by thermal evaporation with a thickness of about 1.5 nm; (10) Thermal evaporation deposition of C 60 Electron transport layer 12, thickness 15 nm; (11) A SnO2 buffer layer 13 is deposited by ALD with a thickness of 20 nm; (12) depositing an IZO transparent conductive layer 14 by magnetron sputtering with a thickness of 70 nm; (13) The second silver electrode 15 is deposited by thermal evaporation with a thickness of 500 nm.
[0060] Example 2 The perovskite / crystalline silicon tandem solar cell of Example 2 was prepared by referring to the preparation method of Example 1, except that in Example 2, "O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol" in step (8) was replaced by "O-(2-aminoethyl)polyethylene glycol".
[0061] Example 3 The perovskite / crystalline silicon tandem solar cell of Example 3 was prepared by referring to the preparation method of Example 1, except that in Example 3, the "O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol" in step (8) was replaced by "O-(3-carboxypropyl)-O′-[2-(3-mercaptopropionylamino)ethyl]-polyethylene glycol".
[0062] Example 4 The perovskite / crystalline silicon tandem solar cell of Example 4 was prepared by referring to the preparation method of Example 1, except that in Example 4, the "O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol" in step (8) was replaced by "O-(2-aminoethyl)-O′-(2-carboxyethyl)polyethylene glycol 3000 hydrochloride".
[0063] Example 5 The perovskite / crystalline silicon tandem solar cell of Example 5 was prepared by referring to the preparation method of Example 1, except that the thickness of the inorganic framework layer obtained in step (7) of Example 5 was 255 nm, and the thickness of the perovskite layer 10 obtained in step (8) was 500 nm.
[0064] Example 6 The perovskite / crystalline silicon tandem solar cell of Example 6 was prepared by referring to the preparation method of Example 1, except that the thickness of the inorganic framework layer obtained in step (7) of Example 6 was 700 nm, and the thickness of the perovskite layer 10 obtained in step (8) was 1200 nm.
[0065] Example 7 The perovskite / crystalline silicon stacked solar cell of Example 7 was prepared by referring to the preparation method of Example 1, except that step (7) in Example 7 was as follows: an inorganic framework layer of PbI2 and CsBr was simultaneously evaporated by an evaporation method, and the substrate laminated with the inorganic framework was subjected to a first annealing. The temperature of the first annealing was 150° C., the annealing time was 5 min, and the thickness of the obtained inorganic framework layer was 450 nm. The evaporation rate of PbI2 was 1.2 Å / s, and the evaporation rate of CsBr was 0.8 Å / s.
[0066] Example 8 The perovskite / crystalline silicon stacked solar cell of Example 8 was prepared by referring to the preparation method of Example 1, except that step (7) in Example 8 was as follows: an inorganic framework layer of PbI2 and CsBr was simultaneously evaporated by an evaporation method, and the substrate laminated with the inorganic framework was subjected to a first annealing. The temperature of the first annealing was 150° C., the annealing time was 5 min, and the thickness of the obtained inorganic framework layer was 450 nm. The evaporation rate of PbI2 was 0.8 Å / s, and the evaporation rate of CsBr was 0.4 Å / s.
[0067] Example 9 The perovskite / crystalline silicon stacked solar cell of Example 9 was prepared by referring to the preparation method of Example 1, except that step (7) in Example 9 was: simultaneously evaporating the inorganic framework layer of PbI2 and CsBr by evaporation, and drying. The thickness of the obtained inorganic framework layer was 450 nm. The evaporation rate of PbI2 was 1.4 Å / s, and the evaporation rate of CsBr was 0.5 Å / s.
[0068] Example 10 The perovskite / crystalline silicon tandem solar cell of Example 10 was prepared by referring to the preparation method of Example 1, except that step (8) in Example 10 was as follows: O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol and FAI, FABr, MACl, and MASCN were dissolved in isopropanol to prepare an organic salt solution, wherein the mass ratio of the amino group-containing PEG derivative (O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol) to the organic salt solution was 1:30; the organic salt solution was coated on the inorganic framework layer by a slit coating method at a coating speed of 15 mm / s, a liquid discharge speed of 15 uL / s, and a Gap of 50 µm; and the substrate coated with the organic salt solution was pre-annealed and then annealed for the second time to prepare a wide bandgap perovskite layer 10 (Cs 0.1 MA 0.15 FA 0.75 PbI 2.4 Br 0.6 ), the band gap of the perovskite layer 10 is about 1.68 eV and the thickness is 600nm; wherein the annealing temperature of the pre-annealing is 90°C, the annealing time is 2min, and the annealing environment is air; the annealing temperature of the second annealing is 150°C, the annealing time is 20min, and the annealing environment is air with a relative humidity of 40%; the area of the perovskite layer prepared in step (8) of this embodiment is 16cm 2 .
[0069] Embodiment 11 The perovskite / crystalline silicon tandem solar cell of Example 11 was prepared by referring to the preparation method of Example 1, except that step (8) in Example 11 was as follows: O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol and FAI, FABr, MACl, and MASCN were dissolved in isopropanol to prepare an organic salt solution, wherein the mass ratio of the amino group-containing PEG derivative (O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol) to the organic salt solution was 1:30; the organic salt solution was coated on the inorganic framework layer by a slit coating method at a coating speed of 50 mm / s, a liquid discharge speed of 50 uL / s, and a Gap of 120 µm; and the substrate coated with the organic salt solution was pre-annealed and then annealed for the second time to prepare a wide bandgap perovskite layer 10 (Cs0.1 MA 0.15 FA 0.75 PbI 2.4 Br 0.6 ), the band gap of the perovskite layer 10 is about 1.68 eV and the thickness is 600nm; wherein the annealing temperature of the pre-annealing is 90°C, the annealing time is 2min, and the annealing environment is air; the annealing temperature of the second annealing is 150°C, the annealing time is 20min, and the annealing environment is air with a relative humidity of 40%; the area of the perovskite layer prepared in step (8) of this embodiment is 16cm 2 .
[0070] Example 12 The perovskite / crystalline silicon tandem solar cell of Example 12 was prepared by referring to the preparation method of Example 1, except that step (8) in Example 12 was as follows: O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol and FAI, FABr, MACl, and MASCN were dissolved in isopropanol to prepare an organic salt solution, wherein the mass ratio of the amino group-containing PEG derivative (O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol) to the organic salt solution was 1:30; the organic salt solution was coated on the inorganic framework layer by a slit coating method at a coating speed of 20 mm / s, a liquid discharge speed of 20 uL / s, and a Gap of 40 µm; and the substrate coated with the organic salt solution was pre-annealed and then annealed for the second time to prepare a wide bandgap perovskite layer 10 (Cs 0.1 MA 0.15 FA 0.75 PbI 2.4 Br 0.6 ), the band gap of the perovskite layer 10 is about 1.68 eV and the thickness is 600nm; wherein the annealing temperature of the pre-annealing is 90°C, the annealing time is 2min, and the annealing environment is air; the annealing temperature of the second annealing is 150°C, the annealing time is 20min, and the annealing environment is air with a relative humidity of 40%; the area of the perovskite layer prepared in step (8) of this embodiment is 16cm 2 .
[0071] Embodiment 13 The perovskite / crystalline silicon tandem solar cell of Example 13 was prepared by referring to the preparation method of Example 1, except that step (8) in Example 13 was as follows: O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol and FAI, FABr, MACl, and MASCN were dissolved in isopropanol to prepare an organic salt solution, wherein the mass ratio of the amino-containing PEG derivative (O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol) to the organic salt solution was 1:30; the organic salt solution was coated on the inorganic framework layer by a slit coating method at a coating speed of 20 mm / s, a liquid discharge speed of 20 uL / s, and a Gap of 100 µm; and the substrate coated with the organic salt solution was subjected to a second annealing to prepare a wide bandgap perovskite layer 10 (Cs 0.1 MA 0.15 FA 0.75 PbI 2.4 Br 0.6 ), the band gap of the perovskite layer 10 is about 1.68 eV and the thickness is 600nm; wherein the annealing temperature of the second annealing is 150°C, the annealing time is 20min, and the annealing environment is air with a relative humidity of 40%; the area of the perovskite layer prepared in step (8) of this embodiment is 16cm 2 .
[0072] Embodiment 14 The perovskite / crystalline silicon tandem solar cell of Example 14 was prepared by referring to the preparation method of Example 1, except that step (8) in Example 14 was as follows: O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol and FAI, FABr, MACl, and MASCN were dissolved in isopropanol to prepare an organic salt solution, wherein the mass ratio of the amino group-containing PEG derivative (O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol) to the organic salt solution was 1:30; the organic salt solution was coated on the inorganic framework layer by a slit coating method at a coating speed of 20 mm / s, a liquid discharge speed of 20 uL / s, and a Gap of 100 µm; and the substrate coated with the organic salt solution was pre-annealed and then annealed for the second time to prepare a wide bandgap perovskite layer 10 (Cs 0.1 MA 0.15 FA 0.75 PbI 2.4 Br 0.6 ), the band gap of the perovskite layer 10 is about 1.68 eV and the thickness is 600nm; wherein the annealing temperature of the pre-annealing is 90°C, the annealing time is 2min, and the annealing environment is air; the annealing temperature of the second annealing is 150°C, the annealing time is 20min, and the annealing environment is air with a relative humidity of 60%; the area of the perovskite layer prepared in step (8) of this embodiment is 16cm 2 .
[0073] Embodiment 15 The perovskite / crystalline silicon tandem solar cell of Example 15 was prepared by referring to the preparation method of Example 1, except that step (8) in Example 15 was as follows: O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol and FAI, FABr, MACl, and MASCN were dissolved in isopropanol to prepare an organic salt solution, wherein the mass ratio of the amino group-containing PEG derivative (O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol) to the organic salt solution was 1:30; the organic salt solution was coated on the inorganic framework layer by a slit coating method at a coating speed of 20 mm / s, a liquid discharge speed of 20 uL / s, and a Gap of 100 µm; the substrate coated with the organic salt solution was pre-annealed and then annealed for the second time to prepare a wide bandgap perovskite layer 10 (Cs 0.1 MA 0.15 FA 0.75 PbI 2.4 Br 0.6 ), the band gap of the perovskite layer 10 is about 1.68 eV and the thickness is 600nm; wherein the annealing temperature of the pre-annealing is 90°C, the annealing time is 2min, and the annealing environment is air; the annealing temperature of the second annealing is 150°C, the annealing time is 20min, and the annealing environment is air with a relative humidity of 10%; the area of the perovskite layer prepared in step (8) of this embodiment is 16cm 2 .
[0074] Example 16 The perovskite / crystalline silicon tandem solar cell of Example 16 was prepared by referring to the preparation method of Example 1, except that the area of the perovskite layer prepared in step (8) of Example 16 was 60 cm 2 .
[0075] Embodiment 17 The perovskite / crystalline silicon tandem solar cell of Example 17 was prepared by referring to the preparation method of Example 1, except that the area of the perovskite layer prepared in step (8) of Example 17 was 100 cm 2 .
[0076] Comparative Example 1 The perovskite / crystalline silicon tandem solar cell of Comparative Example 1 was prepared by referring to the preparation method of Example 1, except that O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol was not added to the organic salt solution in step (8) of Comparative Example 1.
[0077] Comparative Example 2 The perovskite / crystalline silicon stacked solar cell of Comparative Example 2 was prepared by referring to the preparation method of Comparative Example 1, except that the area of the perovskite layer prepared in step (8) of Comparative Example 2 was 60 cm 2 .
[0078] Comparative Example 3 The perovskite / crystalline silicon stacked solar cell of Comparative Example 3 was prepared by referring to the preparation method of Example 1, except that step (8) in Comparative Example 3 was as follows: O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol and FAI, FABr, MACl, and MASCN were dissolved in isopropanol to prepare an organic salt solution, wherein the mass ratio of the amino group-containing PEG derivative (O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol) to the organic salt solution was 1:30; the organic salt solution was coated on the inorganic framework layer by spin coating; the substrate coated with the organic salt solution was pre-annealed and then annealed for the second time to prepare a wide bandgap perovskite layer 10 (Cs 0.1 MA 0.15 FA 0.75 PbI 2.4 Br 0.6 ), the band gap of the perovskite layer 10 is about 1.68 eV and the thickness is 600nm; wherein the annealing temperature of the pre-annealing is 90°C, the annealing time is 2min, and the annealing environment is air; the annealing temperature of the second annealing is 150°C, the annealing time is 20min, and the annealing environment is air with a relative humidity of 40%; the area of the perovskite layer prepared in step (8) is 16cm 2 .
[0079] Comparative Example 4 The perovskite / crystalline silicon stacked solar cell of Comparative Example 4 was prepared by referring to the preparation method of Example 1, except that step (8) in Comparative Example 4 was as follows: FAI, FABr, MACl, and MASCN were dissolved in isopropanol to prepare an organic salt solution; the organic salt solution was coated on the inorganic framework layer by a slit coating method at a coating speed of 20 mm / s, a liquid discharge speed of 20 uL / s, and a Gap of 100 µm; the substrate coated with the organic salt solution was pre-annealed and then annealed for the second time to prepare a wide bandgap perovskite layer 10 (Cs 0.1 MA 0.15 FA 0.75 PbI 2.4 Br 0.6), the band gap of the perovskite layer 10 is about 1.68 eV and the thickness is 600 nm; wherein the annealing temperature of the pre-annealing is 90°C, the annealing time is 2 min, and the annealing environment is air; the annealing temperature of the second annealing is 150°C, the annealing time is 20 min, and the annealing environment is air with a relative humidity of 40%; the area of the perovskite layer prepared in step (8) is 16 cm 2 ; Step (9) is: using a slit coating method at a coating speed of 15 mm / s, a liquid outlet speed of 12 µL / s, and a Gap of 100 µm to coat the perovskite layer 10 with a 0.5 mg / mL O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol organic salt solution for passivation treatment, thereby forming a passivation layer with a thickness of about 1.5 nm.
[0080] Comparative Example 5 The perovskite / crystalline silicon stacked solar cell of Comparative Example 5 was prepared by referring to the preparation method of Example 1, except that step (8) in Comparative Example 5 was as follows: FAI, FABr, MACl, and MASCN were dissolved in isopropanol to prepare an organic salt solution; the organic salt solution was coated on the inorganic framework layer by a slit coating method at a coating speed of 20 mm / s, a liquid discharge speed of 20 uL / s, and a Gap of 100 µm; the substrate coated with the organic salt solution was pre-annealed and then annealed for the second time to prepare a wide bandgap perovskite layer 10 (Cs 0.1 MA 0.15 FA 0.75 PbI 2.4 Br 0.6 ), the band gap of the perovskite layer 10 is about 1.68 eV and the thickness is 600 nm; wherein the annealing temperature of the pre-annealing is 90°C, the annealing time is 2 min, and the annealing environment is air; the annealing temperature of the second annealing is 150°C, the annealing time is 20 min, and the annealing environment is air with a relative humidity of 40%; the area of the perovskite layer prepared in step (8) is 16 cm 2 ; Step (9) is: using a spin coating method to coat the perovskite layer 10 with a 0.5 mg / mL O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol organic salt solution for passivation treatment to form a passivation layer with a thickness of about 1.5 nm.
[0081] The following is a performance test of the perovskite / crystalline silicon tandem solar cells provided in Examples 1-17 of the present application and Comparative Examples 1-5. The test results are shown in Table 1.
[0082] Table 1 Performance test results of perovskite / crystalline silicon tandem solar cells of Examples 1-17 and Comparative Examples 1-5
[0083] Referring to the battery performance test results of Example 1 and Comparative Examples 1 and 3, it can be seen that in the embodiments of the present application, introducing an amino-containing PEG derivative into the organic salt solution in the slit coating method can increase the viscosity of the organic salt solution and make its thermal diffusion coefficient uniform, reduce the influence of the wind knife on the shape of the curved liquid surface during the slit coating process, offset the lateral capillary flow of the solute particles, promote the full reaction of the organic salt solution with the inorganic framework, and achieve high-quality and high-reproducibility deposition of large-area perovskites while being compatible with the industrial silicon bottom battery process with a large velvet surface. Figure 2 is a SEM image of the perovskite layer prepared in Example 1 of the present application, Figure 3 is a SEM image of the perovskite layer prepared in Comparative Example 1 of the present application, Figure 4 is the XRD data diagram of the perovskite layer prepared in Example 1 of the present application, Figure 5 is the XRD data diagram of the perovskite layer prepared in Comparative Example 1 of the present application; Figure 2-Figure 3 It can be seen that the film formation condition of the perovskite layer in Example 1 is better than that of the perovskite layer in Comparative Example 1. Figure 4-Figure 5 It can be seen that compared with Comparative Example 1, the reaction between the organic salt solution and the inorganic framework in the perovskite layer in Example 1 is more complete.
[0084] It can also be seen from the battery performance test results of Examples 1 and 5-6 that controlling the thickness of the inorganic framework can optimize the crystallization quality and performance of the perovskite layer, thereby improving the photoelectric conversion efficiency and stability of the perovskite solar cell.
[0085] It can be seen from the battery performance test results of Examples 1 and 7-8 that the evaporation method is used to simultaneously evaporate PbI2 and CsBr to form an inorganic framework layer, and the evaporation rates of PbI2 and CsBr are controlled at the same time to make the distribution of iodine ions and bromide ions more uniform, thereby facilitating the improvement of the film-forming crystallization quality of the perovskite layer, thereby improving the photoelectric conversion efficiency and stability of the perovskite solar cell.
[0086] It can also be seen from the battery performance test results of Examples 1 and 9 that after the inorganic framework is formed and before the organic salt solution is applied, the substrate of the stacked inorganic framework is subjected to a first annealing, and the temperature and time of the first annealing are reasonably controlled. The annealing process helps to remove residual solvents and volatile components in the inorganic framework, promote crystal growth, and facilitate obtaining higher quality perovskite crystals, thereby improving the photoelectric conversion efficiency and stability of the perovskite solar cell.
[0087] It can also be seen from the battery performance test results of Examples 1 and 10-12 that when the organic salt solution is coated by the slit coating method, the coating speed, liquid discharge speed, and Gap are reasonably controlled, and the coating uniformity of the organic salt solution is higher, which is conducive to achieving high-quality and high-reproducibility deposition of large-area perovskite, thereby improving the photoelectric conversion efficiency and stability of perovskite solar cells.
[0088] It can also be seen from the battery performance test results of Examples 1 and 13-15 that after the organic salt solution is applied to form a perovskite layer, pre-annealing and a second annealing are performed in sequence, and the processes of pre-annealing and the second annealing are reasonably controlled. Combining pre-annealing and the second annealing can promote the full reaction of the organic salt solution with the inorganic framework, thereby improving the photoelectric conversion efficiency of the solar cell. The second annealing process also limits the relative humidity of the air, that is, it limits the moisture content in the air, which can further promote the full reaction of the organic salt solution with the inorganic framework, and achieve high-quality and high-reproducibility deposition of large-area perovskites, thereby further improving the photoelectric conversion efficiency of the solar cell.
[0089] It can also be seen from the battery performance test results of Example 1, Examples 16-17 and Comparative Examples 1-2 that in the embodiments of the present application, the introduction of amino-containing PEG derivatives into the organic salt solution in the slit coating method can promote the full reaction of the organic salt solution with the inorganic framework, thereby achieving high-quality and high-reproducibility deposition of large-area perovskites while being compatible with the industrial silicon bottom battery process with a large velvet surface.
[0090] In summary, the preparation method of the perovskite layer in the embodiment of the present application includes: depositing an inorganic framework material on a substrate to be deposited with a perovskite layer to form an inorganic framework; providing an organic salt solution; applying the organic salt solution on the inorganic framework by a slit coating method, and the organic salt solution reacts with the inorganic framework material to form a perovskite layer; wherein the organic salt solution includes an organic salt, an organic solvent, and a PEG derivative containing an amino group. The PEG derivative containing an amino group is introduced into the organic salt solution to increase the viscosity of the organic salt solution and make its thermal diffusion coefficient uniform, reduce the influence of the wind knife on the shape of the curved liquid surface during the slit coating process, promote the full reaction of the organic salt solution with the inorganic framework, and achieve high-quality and high-reproducibility deposition of large-area perovskites while being compatible with the industrial silicon bottom cell process with a large velvet surface.
[0091] The embodiment of the present application further provides a perovskite layer (not shown), which is prepared by the above method.
[0092] An embodiment of the present application provides a photovoltaic module (not shown), which includes a plurality of solar cells connected in series and / or in parallel; wherein at least one solar cell is such as the above-mentioned perovskite / crystalline silicon stacked solar cell, and adjacent solar cells can be connected together by serial welding.
[0093] The embodiment of the present application can provide a photovoltaic system, including the photovoltaic components in any of the above embodiments. The advantages of the above photovoltaic components are also possessed by the photovoltaic system, which will not be repeated here. The above photovoltaic system has a wide range of applications, not only limited to photovoltaic power stations, such as ground power stations, rooftop power stations and water power stations, but also includes various equipment and devices that use solar energy to generate electricity, such as user solar power supplies, solar street lights, solar cars and solar buildings. Of course, it can be understood that the application scenarios of the photovoltaic system are not limited to this, that is to say, the photovoltaic system can be used in all fields where solar energy is required for power generation. Taking the photovoltaic power generation system network as an example, the photovoltaic system may include a photovoltaic array, a junction box and an inverter. The photovoltaic array may be an array combination of multiple photovoltaic components. For example, multiple photovoltaic components may form multiple photovoltaic arrays. The photovoltaic array is connected to a junction box. The junction box can converge the current generated by the photovoltaic array. The converged current flows through the inverter and is converted into the alternating current required by the mains power grid, and then connected to the mains network to realize solar power supply.
[0094] It should be noted that the terms "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc. are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. The orientation words "inside" and "outside" refer to the inside and outside relative to the outline of each component itself. For example, if the device in the accompanying drawings is inverted, the device described as "above other devices or structures" or "above other devices or structures" will be positioned as "below other devices or structures" or "below other devices or structures". Therefore, the exemplary term "above..." can include both "above..." and "below..." orientations. The device can also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatial relative descriptions used here are interpreted accordingly.
[0095] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein, for example. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0096] It should also be noted that "one embodiment", "another embodiment", "embodiment", etc. mentioned in this application refer to the specific features, structures or characteristics described in conjunction with the embodiment included in at least one embodiment generally described in this application. The same expression appearing in multiple places in the specification does not necessarily refer to the same embodiment. Further, when describing a specific feature, structure or characteristic in conjunction with any embodiment, it is claimed that the realization of such feature, structure or characteristic in conjunction with other embodiments also falls within the scope of this application.
[0097] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0098] It should also be noted that the above are only preferred embodiments of the present application, and the patent protection scope of the present application is not limited thereto. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for preparing a perovskite layer, characterized in that: include: depositing an inorganic framework material on a substrate to form an inorganic framework; An organic salt solution is coated on the inorganic framework by a slit coating method, and the organic salt solution reacts with the inorganic framework material to form a perovskite layer; The organic salt solution comprises an organic salt, an organic solvent and a PEG derivative containing an amino group.
2. The method according to claim 1, characterized in that The amino group-containing PEG derivatives include one or more of O-(2-aminoethyl)polyethylene glycol, O,O′-bis[2-(succinylamino)ethyl]polyethylene glycol, O-(3-carboxypropyl)-O′-[2-(3-mercaptopropionylamino)ethyl]-polyethylene glycol, and O-(2-aminoethyl)-O′-(2-carboxyethyl)polyethylene glycol 3000 hydrochloride.
3. The method according to claim 1, characterized in that The inorganic framework material includes one or more of lead iodide, lead bromide, lead chloride, cesium iodide, cesium bromide, and cesium chloride; The organic salt includes one or more of methylammonium iodide, methylammonium bromide, methylammonium chloride, formamidine hydroiodide, formamidine hydrobromide, formamidine hydrochloride, and methylammonium thiocyanate; The organic solvent includes one or more of ethanol, isopropanol and dimethyl sulfoxide.
4. The method according to claim 1, characterized in that: The mass ratio of the amino-containing PEG derivative to the organic salt solution is 1:20-1:
100.
5. The method according to claim 1, characterized in that The thickness of the inorganic framework is 300-600 nm.
6. The method according to claim 1, characterized in that The preparation method of the inorganic framework comprises: using an evaporation method to simultaneously evaporate PbI2 and CsBr to form the inorganic framework layer; wherein the evaporation rate of the PbI2 is 1.0-1.5 Å / s, and the evaporation rate of the CsBr is 0.4-0.6 Å / s.
7. The method according to claim 1, characterized in that After forming the inorganic framework and before coating the organic salt solution, the method further includes: performing a first annealing on the substrate stacked with the inorganic framework; the conditions of the first annealing include: an annealing temperature of 130-170° C. and an annealing time of 2-10 min.
8. The method according to claim 1, characterized in that In the process of coating the organic salt solution on the inorganic frame by the slit coating method, the coating speed is controlled to be 20-40 mm / s, the liquid discharge speed is 20-40 µL / s, and the Gap is 60-100 µm.
9. The method according to claim 1, characterized in that: After applying the organic salt solution, the method further includes: sequentially performing pre-annealing and secondary annealing on the substrate coated with the organic salt solution; wherein the conditions for the pre-annealing include: an annealing temperature of 60-100° C. and an annealing time of 2-10 min; the conditions for the secondary annealing include: an annealing temperature of 140-170° C. and an annealing time of 20-30 min, and the annealing environment is air with a relative humidity of 20-40%.
10. A perovskite layer, characterized in that: The perovskite layer is prepared by the method according to any one of claims 1 to 9.
11. A perovskite / crystalline silicon tandem solar cell, characterized in that: Comprising the perovskite layer as claimed in claim 10.
12. A photovoltaic module, characterized in that: The photovoltaic module comprises a plurality of solar cells connected in series and / or in parallel; wherein at least one solar cell is the perovskite / crystalline silicon tandem solar cell according to claim 11.
13. A photovoltaic system, characterized in that: Comprising the photovoltaic module as claimed in claim 12.
